1996
DOI: 10.1046/j.1365-2559.1996.d01-540.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of Mcl‐1 and bcl‐2 proteins in thymic epithelial tumours

Abstract: Mcl-1 protein is a new member of the bcl-2 protein family. It is believed to be a blocker of apoptosis but might be different from bcl-2 in the control of apoptosis. Using immunostaining of formalin-fixed, paraffin-embedded sections, we investigated the expression of Mcl-1 in 42 thymic epithelial tumours: three medullary thymomas, five mixed thymomas, seven cortical thymomas, eight well-differentiated thymic carcinomas, 14 squamous cell carcinomas, four lymphoepithelioma-like carcinomas and one undifferentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 9 publications
(21 reference statements)
2
20
0
Order By: Relevance
“…The intracellular distribution of Mcl-1 is essentially mitochondrial (41), being physiologically expressed in many types of long-lived cells (13) and frequently overexpressed in neoplasms. Mcl-1 expression in neoplasms does not follow an obvious pattern, so although it increases with stage or histologic grade in tumors of the thymus (18) and prostate (15) and non-Hodgkin lymphomas (17), it decreases in the more poorly differentiated neuroblastomas (14) and colorectal carcinomas (42).…”
Section: In Patients Who Have Aids-ksmentioning
confidence: 99%
“…The intracellular distribution of Mcl-1 is essentially mitochondrial (41), being physiologically expressed in many types of long-lived cells (13) and frequently overexpressed in neoplasms. Mcl-1 expression in neoplasms does not follow an obvious pattern, so although it increases with stage or histologic grade in tumors of the thymus (18) and prostate (15) and non-Hodgkin lymphomas (17), it decreases in the more poorly differentiated neuroblastomas (14) and colorectal carcinomas (42).…”
Section: In Patients Who Have Aids-ksmentioning
confidence: 99%
“…The largest clinical report by Blumberg and colleagues [12] showed that innominate vessel invasion was the only prognostic factor and that Masaoka stages could not predict prognosis. We treated 40 patients with thymic carcinoma from July 1988 to January 2002, and we reported that thymic carcinomas had a high percentage of bcl-2 and mcl-1 expression [13,14], which indicated their malignant behavior. Those patients, especially with stage III tumors involved in a wide range of different mediastinal organs, were aggressively treated by surgery.…”
mentioning
confidence: 99%
“…Most thymomas and thymic carcinomas were negative for Bcl-xL, and the expression of Bax was inconsistent among different histological types of TET [52]. High-grade thymic carcinomas, especially squamous cell carcinomas, revealed statistically significant higher intensity of Mcl-1 immunoreactivity as compared to other subtypes of TET [34]. Thus, Mcl-1 protein could be a useful marker to differentiate aggressive TET from indolent ones.…”
Section: Expression Of Cell Cycle and Apoptosis Regulators In Thymic mentioning
confidence: 94%
“…Immunohistological studies on mouse and human thymuses revealed that the Bcl-2 family members are differentially expressed in TEC and thymocytes [32,34,[41][42][43][44][52][53][54]. For instance, (a) the expression levels of Bcl-2, Mcl-1, Bim and Bax were higher in medullary than in cortical thymocytes, whereas Bcl-xL exhibited the opposite expression pattern, (b) the expression levels of Bax, Bak, Bad and Mcl-1 were higher in medullary than in cortical TEC and Bcl-2 was expressed by some medullary TEC and (c) Bid was frequently expressed by thymocytes and medullary TEC [32].…”
Section: Expression Of Cell Cycle and Apoptosis Regulators In Thymusmentioning
confidence: 99%